Managerial Communication: A Finger on the PulseTimmPaul R. Managerial Communication: A Finger on the Pulse. Engelwood Cliffs, N.J.: Prentice-Hall, 1980, 386 pp., $14.95. - Farace, Richard V. (Academy of Management Review, 1981)
The article reviews the book ?Managerial Communication: A Finger on the Pulse,? by Paul R. Timm.